Light‐Driven Wide‐Range Nonmechanical Beam Steering and Spectrum Scanning Based on a Self‐Organized Liquid Crystal Grating Enabled by a Chiral Molecular Switch. Issue 2 (31st October 2014) - Jau, Hung‐Chang; Li, Yannian; Li, Cheng‐Chang; Chen, Chun‐Wei; Wang, Chun‐Ta; Bisoyi, Hari Krishna; Lin, Tsung‐Hsien; Bunning, Timothy J.; Li, Quan
<x xml:space="preserve">Abstract</x> Optically controlled wide‐range beam steering and spectrum scanning are demonstrated by a self‐organized liquid crystal grating. The diffraction angle can be tuned around 30° upon light irradiation. In addition, a reversible spectrum scanning system can be constructed using the optical tunable grating. This highly tunable light‐driven grating has great potential in light propagation control and spectroscopy applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>